The Weakness of Family Education in Online Domino Game Addicts in West Pasaman District - Iswandi; Budio, Sesra; Septiana, Yulda Dina; Lestari, Indah Dwi (Insight School Academy, 2025)
Introduction to The Problem: Family is the first educational institution that children go through, and the mother becomes the first madrasah for children, determining the continuation of the next educational process. High domino online game addicts are widely spread in West Pasaman Regency. Addicts consist of teenagers and parents. The family education process for online game addicts is often constrained. Purpose: This study aims to examine the dynamics of family education in high domino online game addicts in West Pasaman Regency. Design/methods/approach: This study uses a qualitative method with a case study approach. Data sources are taken through individual and group interviews with seven informants selected using purposive sampling techniques. The informants in question are the head of the family, wife, and children. Findings: The results of the study indicate that related to the disorientation of family education of high-level online domino game addicts in West Pasaman Regency, namely: i) High-level online domino game addicts spend their nights playing games and ignore their children's education patterns at home. ii) The emotional condition of high-level online domino game addicts is unstable; when they win, they feel happy, and when they lose, they often say dirty words, which are likely to be imitated by children at home. iii) Money from the game is often used for family needs. Originality/value: Based on this study, serious efforts are needed from the authorities to eradicate online gambling.